Analisis Penerapan Standar Akuntansi Pemerintah Berbasis Akrual Pada Laporan Keuangan Badan Layanan Umum Daerah (BLUD) (Studi Kasus Pada BLUD Puskesmas Cidadap) - Aizah Rahayu; Idang Nurodin; Sulaeman Sulaeman (Magister Ilmu Akuntansi Universitas Jambi, 2023)
The purpose of this study was to find out that the presentation of financial reports at the BLUD of the Cidadap Health Center is in accordance with Accrual-Based Government Accounting Standards which refer to Government Regulation Number 71 of 2010 concerning Government Accounting Standards and Permendagri Number 79 of 2018 concerning Regional Public Service Agencies. The research method used in this study is a qualitative method with a descriptive approach by comparing theory and practice in presenting financial reports, data collection techniques used by observation, interviews and documentation. The results of the study show (1) of the 7 accrual-based financial component indicators BLUD Cidadap Health Center in its financial management has implemented SAP in accordance with Government Regulation Number 71 of 2010 concerning Government Accounting Standards on an accrual basis which presents Budget Realization Reports (LRA), Budget Balance Reports More (LSAL), Statement of Cash Flows (LAK), Balance Sheet, Operational Report (LO), Report of Changes in Equity (LPE), and Notes to Financial Statements (CaLK). (2) Financial management staff have PNS status but are not professionals in the financial sector, so it can be said that they are not fully in accordance with what is regulated by Permendagri Number 79 of 2018 concerning Regional Public Service Agencies.